Dehydration of Organic Solutions by a Recirculated Air Sweep Pervaporation Process Using Anion-Exchange Hollow Fibers - Korngold, Emanuel; Zisner, Elisheva; (Tuvia) Bejerano, Tony (Journal of Membrane and Separation Technology, 2016)
An air sweep pervaporation process with thin anion-exchange hollow fibers was investigated for various water-organic solvent mixtures at different operating conditions. It was found that flux and separation factor increased with a decrease of the dielectric constant of the organic solvent. When the temperature of the process was increased, the flux increased. At feed temperatures of 65–70°C it was possible to reduce the water concentration in a 3–10% isopropyl alcohol (IPA) solution to 0.5%. The energy requirement for decreasing the water concentration in IPA from 3–10% to 0.5% was 100–225 kWh ton-1.